1998
DOI: 10.1074/jbc.273.16.9711
|View full text |Cite
|
Sign up to set email alerts
|

Cleavage of BP180, a 180-kDa Bullous Pemphigoid Antigen, Yields a 120-kDa Collagenous Extracellular Polypeptide

Abstract: The hemidesmosome (HD) is a cell-to-substrate adhesion apparatus found in stratified and complex epithelia. One of the putative cell-matrix adhesion molecules present in the HD is the 180-kDa bullous pemphigoid antigen (BP180), also termed type XVII collagen. In our previous study, using a monoclonal antibody (mAb) 1337, we have detected a 120-kDa collagenase-sensitive polypeptide in the HD fraction (Uematsu, J. and Owaribe, K. (1993) Cell Struct. Funct. 18, 588 (abstr.)). The present study was undertaken to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
124
0
5

Year Published

1998
1998
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(135 citation statements)
references
References 46 publications
6
124
0
5
Order By: Relevance
“…Both transmembrane collagens XIII and XVII are proteolytically released from cell surface to the extracellular matrix (7,8,31), which allows them to function as matrix proteins, contributing to cell adhesion and migration. We have recently shown that the ␣ 1 ␤ 1 integrin, rather than ␣ 2 ␤ 1 , is a cellular receptor for type XIII collagen (17).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both transmembrane collagens XIII and XVII are proteolytically released from cell surface to the extracellular matrix (7,8,31), which allows them to function as matrix proteins, contributing to cell adhesion and migration. We have recently shown that the ␣ 1 ␤ 1 integrin, rather than ␣ 2 ␤ 1 , is a cellular receptor for type XIII collagen (17).…”
Section: Discussionmentioning
confidence: 99%
“…Type XVII collagen is shed from the cell surface (7,8), which 2 ) with heat-denatured (dCOL15) human recombinant COL15 domain of collagen type XVII overnight. HaCaT cells (10,000 cells/well) were allowed to attach and spread for 120 min in the presence of synthetic COL15-derived peptides in the concentration of 0.01 or 0.1 mM (A).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Collagen XVII Is Shed by ADAMs-A landmark feature of collagen XVII is its constitutive shedding yielding a shorter and soluble form of the molecule (17,25) that essentially spans the entire ectodomain (see Fig. 2S in supplemental material).…”
Section: Biochemical Features and Ligand Interactions-collagenmentioning
confidence: 99%
“…To address these issues, we produced rabbit antibodies specifically reacting with N-terminal cleavage sites of the shed COL17 ectodomain. COL17 is a type II-oriented transmembrane glycoprotein whose N-terminus and C-terminus are in the cytoplasm and the extracellular matrix (ECM), respectively 10,11 . As is true for other transmembrane collagen family members, the extracellular domain of COL17 can be cleaved from the cell surface in vitro by a disintegrin and metalloproteases (ADAMs) 9, 10 and 17 12, 13 , and interestingly, the ectodomain shedding occurs within the NC16A domain which contains major epitopes for BP autoAbs 14, 15 .…”
mentioning
confidence: 99%